A variant in KCNQ1 gene predicts metabolic syndrome among northern urban Han Chinese women - Yafei Liu; Chunxia Wang; Yafei Chen; Zhongshang Yuan; Tao Yu; Wenchao Zhang; Fang Tang; Jianhua Gu; Qinqin Xu; Xiaotong Chi; Lijie Ding; Fuzhong Xue; et al. (BMC, 2018)
Abstract Background Previous studies have reported that the potassium voltage-gated channel subfamily Q member 1 (KCNQ1) gene is associated with diabetes in both European and Asian population. This study aims to find a predictable single nucleotide polymorphism (SNP) to predict the risk of metabolic syndrome (MetS) through investigating the association of SNP in KCNQ1 gene with MetS in Han Chinese women of northern urban area. Methods Six SNPs were selected and genotyped in 1381 unrelated women aged 21 and above, who have had physical check-up in Shandong Provincial Qianfoshan Hospital. Cox proportional model was conducted to access the association between SNPs and MetS. Results Sixty one women developed MetS between 2010 and 2015 during the 3055 person-year of follow-up. The cumulative incidence density was 19.964/1000 person-year. The SNP rs163182 was associated with MetS both in the additive genetic model (RR = 1.658, 95% CI: 1.144-2.402) and in the recessive genetic model (RR = 2.461, 95% CI: 1.347-4.496). It remained significant after adjustment. This relationship was also observed in MetS components (BMI and SBP). Conclusion A novel association between rs163182 and MetS was found in this study, which can predict the occurrence of MetS among northern urban Han Chinese women. More investigations are needed to be done to assess the possible pathway in which KCNQ1 gene affects MetS.